GMAT Club

Kudos owned by the user


PareshGmat received 4 Kudos for post Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b).

GiverPostDate
Kimberly77Re: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b)29-Oct-2022
schakRe: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b)29-Mar-2017
OreoShakeRe: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b)20-Feb-2016
AhzRe: If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b)02-Aug-2014

Page 1 of 1